1988
DOI: 10.1098/rspb.1988.0038
|View full text |Cite
|
Sign up to set email alerts
|

The reaction-limited kinetics of membrane-to-surface adhesion and detachment

Abstract: Biological adhesion is frequently mediated by specific membrane proteins (adhesion molecules). Starting with the notion of adhesion molecules, we present a simple model of the physics of membrane-to-surface attach­ment and detachment. This model consists of coupling the equations for deformation of an elastic membrane with equations for the chemical kinetics of the adhesion molecules. We propose a set of constitutive laws relating bond stress to bond strain and also relating the chemical rate constants of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
199
1
2

Year Published

1997
1997
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 679 publications
(208 citation statements)
references
References 21 publications
(17 reference statements)
5
199
1
2
Order By: Relevance
“…7). To characterize quantitatively the effect of force on k off , the data were fit to Bell's model of k off as an exponential function of F b (20) and a Hookean spring model of k off as an exponential function of F b 2 as proposed by Dembo et al (21). 2 analysis showed that the fits were good for the Bell model ( 2 ϭ 56.2, with 112 df) and the Hookean spring model ( 2 ϭ 82.4, with 112 df) for the combined data from HL-60 cells and neotrophils.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…7). To characterize quantitatively the effect of force on k off , the data were fit to Bell's model of k off as an exponential function of F b (20) and a Hookean spring model of k off as an exponential function of F b 2 as proposed by Dembo et al (21). 2 analysis showed that the fits were good for the Bell model ( 2 ϭ 56.2, with 112 df) and the Hookean spring model ( 2 ϭ 82.4, with 112 df) for the combined data from HL-60 cells and neotrophils.…”
Section: Resultsmentioning
confidence: 99%
“…Rolling and firmly adherent populations of cells often coexisted. These are the types of results that are predicted based on dynamic simulations of cell adhesive interactions in shear flow (12) or by some peeling models (21) and contrast with results with selectins. One remarkable property of selectins is the lack of development of firm adhesion in the absence of shear flow.…”
Section: Discussionmentioning
confidence: 99%
“…Ce travail démontre la réalité d'un concept imaginé par un théoricien, Micah Dembo, quinze ans auparavant [2]. Il marque aussi une étape supplémentaire dans un domaine de recherche qui s'est montré très actif au cours de la dernière décennie: l'observation directe des liaisons moléculaires individuelles [3].…”
Section: Liaisons « Accrocheuses » Et Mécanique Moléculaireunclassified
“…Cette rupture constitue un événement aléatoire que l'on peut comparer, en quelque sorte, à la désin-tégration d'une substance radioactive. Quelques années plus tard, M. Dembo et al [2] glissantes» (slip bonds) dont la constante de dissociation était -conformément à l'intuition -augmentée par une force de séparation, d'hypothétiques «liaisons accrocheuses» (catch bonds) qui présenteraient un comportement opposé. Bien sûr, le comportement du rapport k on /k off est le même pour les deux types de liaisons, puisque ce rapport est déterminé par les lois de la thermodynamique.…”
Section: Les Sélectinesunclassified
“…The catch-slip binding transitions were discovered recently in a number of receptor-ligand biological complexes. 2,3,7,8,10,17,18,[21][22][23][24]26,27,32 The disulfide bond presents the first example of a chemical catch-bond, i.e., a system in which the increased lifetimes are associated with breaking a covalent bond.…”
Section: Introductionmentioning
confidence: 99%